Analysis of Determinants of the Use of Financial Technology (E-Wallet) among Generation Z - Poddala, Paramita; Alimuddin, Mariani; Bine', Enjelin (Association Of Indonesian Entrepreneurship Study Programs, 2024)
This study presents a Determinant Analysis of the Use of Financial Technology (e-wallets) among Generation Z. Multiple regression analysis methods process the qualitative data used in this research. We used an explanatory research design based on our tests' results. The study asserts that convenience (X1), satisfaction (X2), security (X3), and promotions (X4) influence the use of e-wallets, suggesting that generation Z frequently utilizes financial technology (E-Wallet) for account management, money transfers, and real-time financial activity monitoring. The study uses the following keywords: E-Wallet, Convenience, Satisfaction, Security, Promotion, and Generation Z